On the time-domain electromagnetic response of a conductive permeable sphere - Asten, Michael W. (Journal of applied geophysics, 2009)
The time-domain EM response of a conducting sphere has been subject of past studies with a particular goal of understanding the response of steel unexploded ordnance items. A change in formulas and parameter definition between authors has created inconsistency between published results and analytic formulas. Correction of formulas is required for further studies based on the conducting permeable sphere.